Strategy for Developing the Concept of Halal Beach Tourism in Gunung Kidul Regency, Yogyakarta - Resfa Fitri; Muhammad Wildan Syakuro; Mohammad Iqbal Irfany (Department of Islamic Economics, IPB University, 2023)
One sector that is currently being featured in Indonesia is the development of tourism including halal tourism. The concept of halal is trending ranging from culinary, fashion, cosmetics and even the tourism sector. Gunung Kidul Regency of Yogyakarta has the largest beach tourism area and has the potential to be developed into halal beach tourism. However, appropriate strategy for the development of halal beach tourism in Gunung Kidul Regency is still lacking. Study on the topic on the halal beach tourism is also still limited. This study aims to analyze the strategy for developing the potential of halal beach tourism in Gunung Kidul Regency using the Analytic Hierarchy Process (AHP) method and the Strengths, Weaknesses, Opportunities, and Threats (SWOT) approach. The results of this study show that strength is a top priority in developing halal beach tourism in Gunung Kidul Regency. The strategy priorities are: a) improvement of facilities such as prayer facilities and supporting facilities with the concept of halal beach tourism, b) expanding cooperation with various parties and synergies between beaches, c) improving the quality of human resources through training activities and introducing the concept of halal beach tourism, d) designing an integrated promotion and marketing strategy, and e) improvement of services and providing tour guides for tourists. This research implicates for the establishment of a halal certification policy for entrepreneurs as well as promoting clear regulations on halal beach tourism, especially in Gunung Kidul Regency.